Boom with the social media - Mansor, Noraien; Abd Rahim, Normaliza (Penerbit Universiti Malaysia Terengganu, 2017)
Effective teaching methods and resources have to be taken much emphasis to promote active participation and interaction of students in classroom activities. Social media is gaining tremendous favour in the educational system specifically in the field of language teaching and learning, as such, the possibilities for social media in education are equally exciting as it is a platform to enhance students’ education. Thus, we provide various types of social media applications that is possible to be implemented in English as a Second Language Classroom namely facebook, email, instagram, twitter and blogs. We explore the past researches that have been done and look at the impact of the social media as well as identify issues and ways to overcome the problems related to using social media in ESL classroom. Additionally, we insert the steps for creating new accounts to assist the newcomers of social media. We strongly believe that this publication will be of great assistance to language teachers and learners to be involved in the era of global technology.